Hubungan Pengetahuan dan Faktor yang Mempengaruhi Ibu Nifas dalam Pemberian MP-ASI Terlau Dini pada Bayi Berusia 0-6 Bulan - Dessy Rahelia Siagian; Dwi Febriani Hayuningtyas; Ester Rina Sitorus; Ridha Syahputri Pasaribu (Cerdika: Jurnal Ilmiah Indonesia, 2022)
The nutritiona status of children becomes one of the progress of a nation that is influenced and determined by the level of heath. Breast milk companion food is a food or drink containing nutrients, given to infants or children aged > 6-24 months to meet nutritiona needs other than breast milk. However, in reaity the exclusive breastfeeding until the age of 6 months is difficult for mothers to do. Meanwhile, this can be a hoard of triggers from heath problems for babies caused by the provision of complementary food breast milk too early. Babies become more easily sick, ranging from cough, runny nose, fever, constipation, or diarrhea. This study was conducted in Posyandu Anjelir Desa Sei Semayang in April 2022 and the sample taken was a mother who had a baby aged 0-6 months as many as 31 samples. The design of the research carried out is cross sectiona anaitic with the type of research is quantitative. Data capture using questionnaires, research, univariate and bivariate data anaysis. The results of research conducted with the Chi-Square statistica test found a significant relationship between the level of knowledge and influencing factors (education, employment, parity, and family support) in the provision of breast milk companion food too early with the value obtained p-value (< 0.05). Advice that can be shared for heath workers working in Posyandu is that it can be expected to continue to provide guidance and insight into Exclusive Breast Milk and MP-ASI in a timely manner. With this, the mother and family do not get the wrong information for the heath of the mother and the baby.